SIMULATION OF XRF SPECTRA EMPLOYING A MODIFIED MCNP CODE - Nguyen Thi Tho; Nguyen Kien Cuong; Huynh Ton Nghiem (Tạp chí Khoa học Đại học Đà Lạt)
The Monte Carlo N-Particle code (MCNP4C2 version) has been modified for atomic relaxation in both source code and library to simulate XRF spectra for different measurement configurations. The modified code was then used to simulate XRF spectra of six metal samples: Ni, Cu, Zn, Pd, Ag, Au, and Au alloys on an XRF spectrometer. The results are compared to those of experimental measurements. The intensity ratios of line pairs Kb1/Ka1 and Lb1/La1 between simulated and experimental values differ by about 4%-11% for the six single metals. The relative intensities of the Au alloys, compared to AuLa1, were in the range of 0.02%-26.00%. The modified MCNP4C2 code is capable of forecasting the basic characteristics of new XRF designs.